2018
DOI: 10.3747/co.25.3707
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia–Telangiectasia Gene (ATM) Mutation Heterozygosity in Breast Cancer: A Narrative Review

Abstract: Background Despite the fact that heterozygosity for a pathogenic ATM variant is present in 1%-2% of the adult

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 71 publications
(97 reference statements)
0
56
0
1
Order By: Relevance
“…Exceptions to this definition were made for couples who were carrier matches but were not classified as being at risk to have an affected fetus, specifically those who were both silent alpha thalassemia carriers and those with the R229Q variant in NPHS2 that unless when co‐inherited with specific variants is not believed to cause steroid resistant nephrotic syndrome . Additionally, couples were not considered at‐risk if there was a chance for their offspring to inherit a heterozygous pathogenic variant that could present with adult‐onset symptoms in carriers (such as for GBA, and ATM, among others).…”
Section: Methodsmentioning
confidence: 99%
“…Exceptions to this definition were made for couples who were carrier matches but were not classified as being at risk to have an affected fetus, specifically those who were both silent alpha thalassemia carriers and those with the R229Q variant in NPHS2 that unless when co‐inherited with specific variants is not believed to cause steroid resistant nephrotic syndrome . Additionally, couples were not considered at‐risk if there was a chance for their offspring to inherit a heterozygous pathogenic variant that could present with adult‐onset symptoms in carriers (such as for GBA, and ATM, among others).…”
Section: Methodsmentioning
confidence: 99%
“…Differently from A-T patients, who carry almost exclusively nonsense truncating mutations, cancer patients bear more heterogeneous types of variants. These include out-of-frame mutations with premature stop-codon formation, splicing-affecting variants, synonymous, missense and intronic mutations, with much less evident functional impact, and are enriched in VUS [71,75]. In the last decade, it has been shown that cell models with ATM mutations that cause low or no protein expression are more sensitive to PARPi, supporting clinical implications similar to those of BRCA1/2 mutant carriers.…”
Section: Atm Variants and A New Possible Functional Assay: The P53 MImentioning
confidence: 98%
“…Up to 2% of the whole human population is heterozygous for a pathogenic ATM variant and it has been demonstrated that healthy carriers, such as the parents of A-T patients, are more susceptible to tumor formation, with a 5-to 9-fold increased risk of breast cancer in women [69,70]. Heterozygotes are also sensitive to damage from radio-and chemo-therapy [69][70][71][72][73]. Moreover, it has been demonstrated that rare missense variants of moderate-risk genes, such as ATM, confer an increased risk for early-onset breast cancer [74].…”
Section: Atm Variants and A New Possible Functional Assay: The P53 MImentioning
confidence: 99%
“…Homozygous mutations in ATM gene cause ataxiatelangiectasia, cerebellar ataxia associated immunodeficiency syndrome 10 , while heterozygous mutations predispose to pancreatic and prostate cancer, particularly in women with breast cancer. Life-long breast cancer risk is up to 25% in women with pathogenic heterozygous ATM mutations 11 . Both pathogenic variants of ATM are a nonsense alteration.…”
Section: Discussionmentioning
confidence: 99%